Development and Evaluation of a Cryopreserved Whole-Parasite Vaccine in a Rodent Model of Blood-Stage Malaria - Danielle I. Stanisic; Mei-Fong Ho; Reshma Nevagi; Emily Cooper; Maddison Walton; Md Tanjir Islam; Waleed M. Hussein; Mariusz Skwarczynski; Istvan Toth; Michael F. Good (mBio, 2021)
Malaria is a mosquito-borne infectious disease that is caused by parasites of the genus, PlasmodiumPlasmodiumP. falciparum